2011
DOI: 10.1016/j.chom.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair Proteins Are Directly Involved in Regulation of Gene Expression during Plant Immune Response

Abstract: Systemic acquired resistance (SAR), an inducible plant-defense response to local infection, requires the signaling molecule salicylic acid (SA) and the transcriptional coactivator NPR1, with concerted activation of pathogenesis-related (PR) genes. Arabidopsis sni1 is an npr1 suppressor and derepression of defense genes in sni1 causes reduced growth and fertility and increased homologous recombination. Characterizing suppressors of sni1, we identify the DNA damage repair proteins SSN2 and RAD51D as genetic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 37 publications
(58 reference statements)
1
76
1
1
Order By: Relevance
“…For instance, SNI1 (Suppressor of NPR1, Inducible) was proposed to mediate defence gene expression via histone modification 44 . Interestingly, several ssn mutants encode mutated versions of well-established DNA R/R proteins, such as RAD51D (SSN1), SWI/SNF (SSN2) and BRCA2A (SSN3) 30,45,46 . Mutations in any of the three SSN genes results in altered induction of pathogen-responsive genes and increased susceptibility/sensitivity to pathogens and DNAdamaging agents.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, SNI1 (Suppressor of NPR1, Inducible) was proposed to mediate defence gene expression via histone modification 44 . Interestingly, several ssn mutants encode mutated versions of well-established DNA R/R proteins, such as RAD51D (SSN1), SWI/SNF (SSN2) and BRCA2A (SSN3) 30,45,46 . Mutations in any of the three SSN genes results in altered induction of pathogen-responsive genes and increased susceptibility/sensitivity to pathogens and DNAdamaging agents.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Bao et al (2013) found an unexpected link between cell cycle progression and plant immunity, suggesting that cell cycle misregulation impacts the expression of R genes. Also, DNA repair proteins have been shown to be directly involved in the regulation of gene expression during plant defense responses (Song et al, 2011). The DNA damage response is an intrinsic component of the plant immune response and, in turn, enhances salicylic acid-mediated defense gene expression (Yan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis Columbia-0 recombination reporter line 1445 containing partial inverted repeats of the GUS gene has been used by several groups as it is one of the best lines reporting biotic stress-related events (Molinier et al, 2006;Durrant et al, 2007;Wang et al, 2010;Song et al, 2011). Since this line was claimed to be homozygous and carries a single copy of the reporter construct (Molinier et al, 2006), we sought to determine from the published literature the location of the transgene in the Arabidopsis genome to determine the structure of the locus and possible effects of the flanking sequences on reconstitution of GUS expression under biotic stress.…”
Section: Poorly Characterized Shr Line 1445mentioning
confidence: 99%